Analisa Pengaruh Attribute, Promotion, Service Quality, dan Social Media Marketing terhadap Image dan Purchase Decision Usaha Oleh-Oleh Kuliner Kota Batam - Yandi Suprapto; Surianti Surianti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine whether attributes, promotion, service quality, and social media marketing can influence image and purchase decisions. The object of research includes consumers of culinary souvenir shops in the city of Batam. Data collection was carried out by distributing questionnaires to 180 respondents. The collected data were processed by using partial least square (PLS). The results found that seven of the eight hypotheses tested had a significant positive relationship. The hypothesis includes attributes to image, promotion to image, service quality to image, attribute to purchase decision, promotion to purchase decision, social media marketing to purchase decision, and image to purchase decision. Meanwhile, service quality on purchase decisions is declared insignificant.